Integration of anaerobic digestion and composting allows safety recovery of energy and nutrients from AFB1 contaminated corn. Issue 5 (October 2022) - Cucina, Mirko; Tacconi, Chiara; Gigliotti, Giovanni; Zadra, Claudia
Abstract: Occurrence of human carcinogen aflatoxin B1 (AFB1) in feed and foodstuffs is expected to increase in the next years due to climate change. This work aimed to assess the possible recovery of energy and nutrients from AFB1 contaminated corn through the integration of anaerobic digestion and composting. Pilot scale anaerobic digestion and composting of the digestate were carried out using AFB1 contaminated corn (100 µg g -1 ) and pig slurry. Biomethane yields, compost quality and AFB1 degradation were evaluated during the trials. Results of this research showed that anaerobic digestion and composting integration can represent a suitable solution for the safe valorisation of a hazardous waste like AFB1 contaminated corn. Neither biomethane yields (214 NL kg -1 VS) nor compost quality were affected from AFB1 contamination (i.e., C/N ratio and germination index of the compost were 10.8% and 100.9%, respectively). In addition, the mycotoxin was completely removed at the end of the process (the concentration was under the detection limit already after the active phase of composting). This confirms that AFB1 contaminated feed and foodstuffs might be safely treated in conventional anaerobic and composting facilities, without negative effects on process stability and products quality. Graphical Abstract: ga1 Highlights: AFB1 contaminated corn was treated by integrated anaerobic digestion and composting. Biomethane yield (214 NL kg -1 VS) was not affected by AFB1 contamination. Digestate composting completely removed AFB1 already after the active phase. Compost was highly stabilized and mature (i.e., C/N ratio was 11 and GI was 101%). Energy and nutrients can be effectively recovered from AFB1 contaminated corn.